Construction a of lattices over number fields and block fading (wiretap) coding - Wittawat Kositwattanarerk (2018)
© 1963-2012 IEEE. We propose a lattice construction from totally real and complex multiplication fields, which naturally generalizes Construction A of lattices from p -ary codes obtained from the cyclotomic field Q(ζp), p a prime, which in turn contains the so-called Construction A of lattices from binary codes as a particular case. We focus on the maximal totally real subfield Q(ζp-r)+ζp-r) of the cyclotomic field Q(ζpr), ≥ 1. Our construction has applications to coset encoding of algebraic lattice codes for block fading channels, and in particular for block fading wiretap channels.